AB0611 STRAIN ANALYSIS OF THE RIGHT VENTRICLE USING 2D-SPECKLE TRACKING ECHOCARDIOGRAPHY IN A COHORT OF PATIENTS WITH SYSTEMIC SCLEROSIS. (2nd June 2020) - Spinella, A.; Macripo', P.; Cocchiara, E.; Galli, E.; Lumetti, F.; Magnani, L.; Coppi, F.; Mattioli, A. V.; Rossi, R.; Boriani, G.; Salvarani, C.; Giuggioli, D.
Abstract : Background: Systemic Sclerosis (SSc) is a rare and life-threatening connective tissue disease with multiple organ impairment. Cardio-pulmonary involvement is common: pulmonary fibrosis, pulmonary hypertension (PH), and electrical disorders are the most serious complications and causes of increased mortality. Objectives: We evaluated features related with the onset and development of PH in a cohort of SSc patients. We further studied ecocardiographic abnormalities, by means of 2D-speckle tracking echocardiography (STE) with specific reference to the right ventricular strain measure (RV-strain). Methods: We analyzed data from 50 SSc patients (pts) referred to our University-based Rheumatology Centre and SSc Unit from January 2007 to June 2019 (F/M 45/5; lc/dcSSc 45/5; mean age 59.20±14.357 years; mean disease duration 12.08±8.75 years). All pts underwent general and cardio-pulmonary assessment in our Cardio-Rheumatology Clinic. The following parameters were considered: blood exams, in particular inflammation indexes, uric acid test and serum autoantibodies; pulmonary function tests; high resolution scan of the lungs (HRCT); standard electrocardiogram (ECG) and RV-strain measured by 2D-STE. These examinations were performed according to clinical picture and current methodologies. We compared SSc subjects with (10/50) and without (40/50) PH diagnosis during follow-up regardless of treatments. Results: SSc pts with PH didn't show significant alterations concerning RV-strain if compared with pts without PH (p=0.707). Nevertheless, RV-strain value was modified in relation to TAPSE alterations in all pts but this data correlated with right ventricular dilatation only in PH subjects. Furthermore, interesting significant values about dilatation of right and left atria (p=0.007, p=0.048), dilatation of inferior vena cava (p=0.037) and right ventricle (p=0.023) were observed. Left ventricular hypertrophy (p=0.012) as well as valvular insufficiencies (mitral and aortic) were more frequent in PH group too (p=0.016). These pts showed higher incidence of skin ulcers (p=0.0001), higher values of blood pressure (p=0.004), elevated uric acid levels (p=0, 027) and anti-centromere antibodies positivity (p=0.0001). Conclusion: Our research provides further evidence of the prognostic value of echocardiographic findings in SSc subjects, with focus on PH. Population enlargement is ongoing in order to identify more accurate results about RV-strain, considering the efficacy of PH treatments on cardiac contractility. Speckle tracking echocardiography proves to be a sensitive, low-cost, non-invasive and reliable tool to detect early cardiac impairment in Ssc, full of potential future prospects. Disclosure of Interests: None declared